The role of physical exercise in prevention and treatment of obesity in adults - Gema Torres Luque; Miguel García-Martos; Carmen Villaverde Gutiérrez; Nuria Garatachea Vallejo (FEADEF, 2010)
Obesity is a chronic, multifactorial, increasing prevalence, which along with being overweight affects more than half the population in developed countries. The aim of this paper is to set basic guidelines regarding the training load, frequency, duration, intensity, etc. in physical activity programs aimed at obese people, propose three concrete guidelines for action. The aim is to contribute to a better understanding of physical activity programs in this population.